2016
DOI: 10.1617/s11527-016-0868-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of superabsorbent polymers (SAP) on the freeze–thaw resistance of concrete: results of a RILEM interlaboratory study

Abstract: This article presents the results of an interlaboratory experimental study performed by 13 international research groups within the framework of the activities of the RILEM Technical Committee 225-SAP ''Applications of Superabsorbent Polymers in Concrete Construction''. Two commercially available superabsorbent polymers (SAP) were tested in terms of their influence on the freeze-thaw resistance of ordinary concrete. To test the robustness of the method, all participating laboratories used locally produced mate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
99
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 147 publications
(100 citation statements)
references
References 16 publications
1
99
0
Order By: Relevance
“…Freeze–thaw resistance tests for concrete have been conducted by setting the SAP dosage and SAP particle size as variables [12]. Recently, the effect of two types of SAPs on the freeze–thaw resistance of concrete in various regions of the world has been reported via the results of an inter-laboratory study [13]. In those studies, reference mixtures with different water-to-cement ratios were compared with respect to the freeze–thaw resistance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Freeze–thaw resistance tests for concrete have been conducted by setting the SAP dosage and SAP particle size as variables [12]. Recently, the effect of two types of SAPs on the freeze–thaw resistance of concrete in various regions of the world has been reported via the results of an inter-laboratory study [13]. In those studies, reference mixtures with different water-to-cement ratios were compared with respect to the freeze–thaw resistance.…”
Section: Introductionmentioning
confidence: 99%
“…Many experimental studies have found that SAP improves the freeze–thaw resistance of concrete [11,12,13,14,15]; however, opposite cases have also been reported [13,14,16]. A possible explanation for these conflicting results could be the complex absorption behavior of SAPs in hardened concrete when the concrete is exposed to water.…”
Section: Introductionmentioning
confidence: 99%
“…With SAPs, the dimensions of the voids are fixed to the swollen state of the SAP during mixing, in contrast to regular air entrainment. Addition of SAPs does not necessarily need to affect the compressive strength [12] and seems to be promising independent from local raw materials and production processes [13]. The scope of this paper was to report an investigation under laboratory conditions on concrete durability by creating a size and shape-designed pore systems using SAP in concrete mixes, as an in alternative to AEA, in order to improve its durability, especially in terms of freeze-thaw resistance.…”
Section: Superabsorbent Polymers (Saps)mentioning
confidence: 99%
“…With SAPs, the dimensions of the voids are fixed to the swollen state of the SAP during mixing, in contrast to regular air entrainment. Addition of SAPs does not necessarily need to affect the compressive strength [12] and seems to be promising independent from local raw materials and production processes [13].…”
Section: Introductionmentioning
confidence: 99%
“…7 schematically represents the modification of cementitious systems by SAP. When capillary pores (10nm-10µm) are analysed, it is expected that SAPs increase total porosity due to macro-pore formation, especially when additional water is considered [34]. In the case of smaller pores, additional amounts of water do not significantly affect micropore range (< 2 nm) and slightly increase mesopore range (2-50 nm) [35].…”
Section: Mechanical Propertiesmentioning
confidence: 99%